Development and validation of an analytical technique to quantify amitraz in a PVC strip formulation used in Varroa mite control in honey bees - Reinaud, Daniel (2018)
Introduction/Objective: Amitraz (AMT) is a formamidine ectoparasiticide used in veterinary medicine to control ticks, lice and mites. It is available for topical use as spray, dip, or pour on in dogs, swine and cattle. Argentina is one of the major honey bee producer countries. The mite Varroa destructor is a pathogenic parasite, which seriously affect honey production by Apis mellifera. It feeds on the haemolymph of brood and adult honey bees, contributing to the spread of viral and bacterial infections. AMT has been approved to use as a sustained-released strip to control varroasis. The goal of the present work was to develop and validate an HPLC analytical methodology to quantify AMT after its recovery from PVC fortified strips (AMIVAR 500®, APILAB S.R.L.). Materials and Methods: AMT quantification was performed by HPLC with UV detection (288 nm). An Agilent Extend-C18 reversed-phase column (4.6 × 250 mm, 5 µm) fitted with a guard column (4.6 × 12.5 mm, 5 µm) was used for separation. Elution was carried out at an isocratic flow (1 ml per min) using a mobile phase composed by 20 mM triethylamine: acetonitrile (10:90). AMT was extracted from PVC strip samples with methylene chloride for 18 h at 20 ± 2°C. The method underwent an exhaustive validation process following internationally recognized standards (CVMP, VICH, 1998). Considering the purpose of the developed analytical method, the following validation parameters were determined: specificity, linearity, range, precision (repeatability, intermediate precision) and recovery. Results and Conclusions: The AMT retention time was a 7.5 min. No interferences from endogenous compounds of the PVC strip sample were observed. The ratio “AMT standard signal/blank noise signal” was much higher than that required to determine the measurable concentration range (20–30 µg ml−1). The calibration parameters achieved the established acceptance criteria, repeatability of the triplicates (intraday repeatability) with a CV ≤ 2% and correlation coefficient ≥ 0.99. The repeatability (CV) and intermediate precision were ≤ 2% or ≤ 4%, respectively. The recovery was 104% so it was proposed not to correct for recovery in the routine analysis. The obtained validation parameters confirm the linearity of the model, offering a good fit for the proposed working range. Thus, the developed analytical methodology complies with the validation criteria required for AMT quantification in PVC strips. The analytical data shown here is a step forward to assure the correct use of AMT to control Varroa mite in honey bee production.